Managerial Overconfidence in the Carbon Shadow: Unveiling Risks in Korean Firms - Kim, Su-In; Park, Sorah; Shin, Heejeong; Shin, Hyejeong (The Korean Academic Association of Business Administration, 2025)
This study examines how overconfident managers affect carbon risk. Using a sample of Korean-listed companies, we find that managerial overconfidence is positively associated with greenhouse gas emissions, suggesting that firms with overconfident managers are less likely to decrease carbon risk. However, the association between managerial overconfidence and carbon risk is attenuated in firms with higher board independence and social performance. Our findings suggest that corporate governance and attitudes toward social responsibility are effective monitors for reducing or hedging overconfident managers’ environmental risk. Our study has practical implications in that, when implementing policies to achieve carbon reduction targets, regulators need to consider the personal attrib utes of corporate executives and monitoring schemes that could work in the interests of stakeholders to improve environmental performance. KCI Citation Count: 0